Benchmarking archaeology degrees at Australian universities : final report part 1, priority project PP653. - Beck, Wendy; Clarke, Catherine (Australian Learning & Teaching Council, 2008)
The major challenge identified for archaeology teaching and learning in Australia is the perceived shortcomings in archaeological qualifications, variously seen as inconsistent and/or unsuited to the goals of either students or employers. We argue that academics, not employers, are responsible for developing explicit understandings and standards for the learning outcomes of archaeology degrees, but that there has been little opportunity for Australian academics to discuss university education in archaeology. We review the Benchmarking Archaeology Degrees project which aimed to incorporate the whole disciplinary community, both academic and professional. Overall, forming and maintaining a shared network of understanding in the disciplinary community a benchmark is seen as critical for enhancing teaching and learning outcomes for students, employers and university staff. Subject benchmarking is valuable both for providing the basis for improved university archaeology teaching and learning, refining curricula, and for throwing light upon continuing issues affecting the discipline. The process of subject benchmarking has many advantages even beyond that of establishing a common set of statements of the knowledge and skills expected of archaeology graduates. This report describes the design, analysis and results of the project, a complementary survey and interview data collection exercise which formed the basis of two national collaborative workshops where the subject benchmarks were articulated and developed. The benchmark document is now being widely disseminated on the Web. [Executive summary]